Peningkatan Pemahaman terhadap Peran TNI dalam Pemberdayaan Masyarakat di Daerah Perbatasan Nusa Tenggara Timur - Posma Sariguna Johnson Kennedy (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The implementation of this community service activity is to conduct discussions aimed at increasing understanding of the duties of the TNI to assist local governments in community empowerment programs at the border of Nusa Tenggara Timur (NTT) Province. The method of writing this paper is to use a qualitative approach by reviewing various literature and discussions conducted with Korem 161/Wirasakti Kupang and Kodim 1605 Belu NTT. At the NTT border, the Border Security Task Force (Satgas Pamtas) 742/SWY TNI performs the main task of Border Security and explores the community's potential, and empowers this potential. There are many creations of this unit in